Prostate cancer follow-up costs in Germany from 2000 to 2015 - Michaeli, Christoph T.; Michaeli, Daniel (Journal of cancer survivorship, 2022)
The main objective of this study is to estimate and evaluate 10-year follow-up costs after prostate cancer treatment with curative (surgery, radiotherapy) and non-curative intent (hormone, androgen deprivation) per patient in Germany in 2000, 2008, and 2015.